Ballistic modeling of InAs nanowire transistors. (January 2016) - Jansson, Kristofer; Lind, Erik; Wernersson, Lars-Erik
Highlights: The intrinsic performance of ballistic InAs nanowire transistors is evaluated. The transport properties within nanowires of different diameters are mapped. The influence from non-parabolic bands and self-consistency is quantified. Scaling of the transistor structure is investigated. Abstract: In this work, the intrinsic performance of InAs nanowire transistors is evaluated in the ballistic limit. A self-consistent Schrödinger–Poisson solver is utilized in the cylindrical geometry, while accounting for conduction band non-parabolicity. The transistor characteristics are derived from simulations of ballistic transport within the nanowire. Using this approach, the performance is calculated for a continuous range of nanowire diameters and the transport properties are mapped. A transconductance exceeding 4 S / mm is predicted at a gate overdrive of 0.5 V and it is shown that the performance is improved with scaling. Furthermore, the influence from including self-consistency and non-parabolicity in the band structure simulations is quantified. It is demonstrated that the effective mass approximation underestimates the transistor performance due to the highly non-parabolic conduction band in InAs. Neglecting self-consistency severely overestimates the device performance, especially for thick nanowires. The error introduced by both of these approximations gets increasingly worse under high bias conditions.